Pectoral Fin Anomalies in tbx5a Knockdown Zebrafish Embryos Related to the Cascade Effect of N-Cadherin and Extracellular Matrix Formation - Jenn-Kan Lu; Tzu-Chun Tsai; Hsinyu Lee; Kai Hsia; Chih-Hsun Lin; Jen-Her Lu (Journal of Developmental Biology, 2019)
Functional knockdown of zebrafish tbx5a causes hypoplasia or aplasia of pectoral fins. This study aimed to assess developmental pectoral fin anomalies in tbx5a morpholino knockdown zebrafish embryos. The expression of cartilage-related genes in the tbx5a morphant was analyzed by DNA microarray, immunostaining, and thin-section histology to examine the detailed distribution of the extracellular matrix (ECM) during different pectoral fin developmental stages. Chondrogenic condensation (CC) in the tbx5a morpholino knockdown group was barely recognizable at 37 h postfertilization (hpf); the process from CC to endoskeleton formation was disrupted at 48 hpf, and the endoskeleton was only loosely formed at 72 hpf. Microarrays identified 18 downregulated genes in tbx5a-deficient embryos, including 2 fin morphogenesis-related (cx43, bbs7), 4 fin development-related (hoxc8a, hhip, axin1, msxb), and 12 cartilage development-related (mmp14a, sec23b, tfap2a, slc35b2, dlx5a, dlx1a, tfap2b, fmr1, runx3, cdh2, lect1, acvr2a, mmp14b) genes, at 24 and 30 hpf. The increase in apoptosis-related proteins (BAD and BCL2) in the tbx5a morphant influenced the cellular component of pectoral fins and resulted in chondrocyte reduction throughout the different CC phases. Furthermore, tbx5a knockdown interfered with ECM formation in pectoral fins, affecting glycosaminoglycans, fibronectin, hyaluronic acid (HA), and N-cadherin. Our results provide evidence that the pectoral fin phenotypic anomaly induced by tbx5a knockdown is related to disruption of the mesoderm and ECM, consequently interfering with mesoderm migration, CC, and subsequent endoskeleton formation.